Paper 2: Climatic Study of the Underground Archaeological Site Coudenberg. (February 2014) - Hayen, Roald; De Clercq, Hilde; Godts, Sebastiaan
<x content-type="archive" xml:space="preserve">Abstract</x> The excavation and valorization of subterranean archaeological remains, and eventually opening a site to the public, required a proper management and conservation strategy. This strategy was based on the evaluation of the delicate balance between the requirements for public health and safety, and the protection of the archaeological remains from future degradation. Controlling the climate can be essential for a preventive conservation strategy, which can be defined as an indirect action to increase the life expectancy of the archaeological remains, and by doing so keeping them in a preferred state of conservation to mitigate damage and/or deterioration. Potential risks and possible interventions are outlined to avoid climatic conditions which are in conflict with the requirements for the visitors' comfort while preventing damage phenomena to the materials.